KESALAHAN PENGGUNAAN KALIMAT EFEKTIF PADA TUGAS KETERAMPILAN MENULIS KARANGAN EKSPLANASI SISWA KELAS XI IPS SMA NEGERI 3 KOTA JAMBI - Sainil Amral; Waode Apria Dega Gaputri (Universitas Batanghari, 2019)
The purpose of this study was to describe the use of effective sentence errors based on the characteristics of effective sentences in explanatory essays of class XI IPS 2 Semester 1 SMA N 3 Kota Jambi Academic Year 2019. This study included descriptive qualitative research. The primary data in this study isseries of sentences that are identified as violating the characteristics of effective sentence use, while the secondary data in this study are supporting data originating from books. Based on the results of the study it can be concluded that the wrong sentences are identified for violating the characteristics of effective sentences in explanatory essays of class XI IPS students semester 1 SMA N 3 Kota Jambi Academic Year 2019 based on four characteristics of effective sentences namely unity, economics, emphasis, and variance. Of the four characteristics, there are errors in the characteristics of the use of effective sentences that are dominant to errors found in the characteristics of unity and economics, while emphasis and variance are not too dominant. From the results of this study, researchers can suggest that writers pay more attention to effective sentences in writing essays and other writings. Keywords: Effective Sentence, Explanatory